Tuesday

March 31, 2015

March 31, 2015

Posted by **K** on Tuesday, November 28, 2006 at 8:21pm.

27^4x-2=243^3x+6

Please explain how to do it.

Thanks

27^(4x-2)=243^(3x+6)

Notice that 27 and 243 are both multiples of 3

Changing them..

(3^4)^(4x-2)=(3^6)^(3x+6)

3^4(4x-2)= 3^6(3x+6)

taking the log base 3 of each side.

(4x-2)= (3x+6)

and solve for x.

That doesn't work if you check it, did you do it wrong?

oops.

27^(4x-2)=243^(3x+6)

Notice that 27 and 243 are both multiples of 3

Changing them..

(3^4)^(4x-2)=(3^6)^(3x+6)

3^4(4x-2)= 3^6(3x+6)

taking the log base 3 of each side.

4(4x-2)= 6(3x+6)

and solve for x.

**Answer this Question**

**Related Questions**

algebra - Solve each equation by factoring. 7x²-243=0 I know I'm supposed to add...

Math - Find X 27^4x-2=243^3x=6 Please Explain Thanks Is this a repeat of the ...

math - 5 people measured a metal bar using the same measuing instrument,but each...

MATH URGENT - The prime factorization of 243 is 3*3*3*3*3. Write 243 as the ...

Algebra II - Please check answers: Use the equation of the exponential function ...

Math - The sum of two counting numbers is 243. Half of one number is four times ...

Sequence - What is the fifth term of the sequence a sub n = 1/3^n? a)1/12 b)1/81...

Math - Evaluate the expression below log 243 9

math - A score of 243 is a "basic" reading level. Scores for a random sample of ...

maths - for this quadratic equation: y2-4y-16 = 0 which two options are correct ...